A VIT‐like transporter facilitates iron transport into nodule symbiosomes for nitrogen fixation in soybean. Issue 5 (28th March 2020) - Liu, Sheng; Liao, Li Li; Nie, Miao Miao; Peng, Wen Ting; Zhang, Meng Shi; Lei, Jia Ning; Zhong, Yong Jia; Liao, Hong; Chen, Zhi Chang
Summary: Effective legume–rhizobia symbiosis depends on efficient nutrient exchange. Rhizobia need to synthesize iron‐containing proteins for symbiotic nitrogen fixation (SNF) in nodules, which depends on host plant‐mediated iron uptake into the symbiosome. We functionally investigated a pair of vacuolar iron transporter like (VTL) genes, GmVTL1a / b, in soybean ( Glycine max ) and evaluated their contributions to SNF, including investigations of gene expression patterns, subcellular localization, and mutant phenotypes. Though both GmVTL1a / b genes were specifically expressed in the fixation zone of the nodule, GmVTL1a was the lone member to be localized at the tonoplast of tobacco protoplasts, and shown to facilitate ferrous iron transport in yeast. GmVTL1a targets the symbiosome in infected cells, as verified by in situ immunostaining. Two vtl1 knockout mutants had lower iron concentrations in nodule cell sap and peribacteroid units than in wild‐type plants, suggesting that GmVTL1 knockout inhibited iron import into symbiosomes. Furthermore, GmVTL1 knockout minimally affected soybean growth under nonsymbiotic conditions, but dramatically impaired nodule development and SNF activity under nitrogen‐limited and rhizobia‐inoculation conditions, which eventually led to growth retardation. Taken together, these results demonstrate that GmVTL1a is indispensable for SNF in nodules as a transporter of ferrous iron from the infected root cell cytosol to the symbiosome.